Comparative selenoproteome analysis reveals a reduced utilization of selenium in parasitic platyhelminthes - Jiang,Liang; Zhu,Hua-Zhang; Xu,Yin-Zhen; Ni,Jia-Zuan; Zhang,Yan; Liu,Qiong (PeerJ, 2013)
Background. The selenocysteine(Sec)-containing proteins, selenoproteins, are an important group of proteins present in all three kingdoms of life. Although the selenoproteomes of many organisms have been analyzed, systematic studies on selenoproteins in platyhelminthes are still lacking. Moreover, comparison of selenoproteomes between free-living and parasitic animals is rarely studied. Results. In this study, three representative organisms (Schmidtea mediterranea, Schistosoma japonicum and Taenia solium) were selected for comparative analysis of selenoproteomes in Platyhelminthes. Using a SelGenAmic-based selenoprotein prediction algorithm, a total of 37 selenoprotein genes were identified in these organisms. The size of selenoproteomes and selenoprotein families were found to be associated with different lifestyles: free-living organisms have larger selenoproteome whereas parasitic lifestyle corresponds to reduced selenoproteomes. Five selenoproteins, SelT, Sel15, GPx, SPS2 and TR, were found to be present in all examined platyhelminthes as well as almost all sequenced animals, suggesting their essential role in metazoans. Finally, a new splicing form of SelW that lacked the first exon was found to be present in S. japonicum. Conclusions. Our data provide a first glance into the selenoproteomes of organisms in the phylum Platyhelminthes and may help understand function and evolutionary dynamics of selenium utilization in diversified metazoans.
Keywords: Selenocysteine; Parasite; Platyhelminthes; Selenoprotein; Bioinformatics